Penguatan Kemampuan Guru Menggunakan Lecture Strategy Dalam Pembelajaran Jarak Jauh (Pjj) Di Tengah Pandemi Covid-19 - Suhardin (Jurnal Syntax Transformation, 2020)
Learning with strategic lectures in a normal atmosphere is often seen as outdated, making students bored in following the lesson. Learning emphasizes student activity and participation by using an active learning strategy. In an atmosphere of Distance Learning in the midst of COVID-19, are there differences in student learning outcomes taught by the lecture strategy and active learning strategy. This article presentation the difference in learning outcomes of the two strategies by carrying out experiment research in two classes at Madrasah Aliyah, the first class is given learning using the lecture strategy and the second class is active learning strategy. This study found that there was a significant difference in learning outcomes between the lecture strategy class and the active learning strategy. Lecture strategy has a very significant effect on increasing student mastery of the learning material provided by the teacher. Thus, in an atmosphere of Distance Learning in the midst of the COVID-19 pandemic, teachers need to strengthen their ability to apply strategic lectures in learning